Moi aussi: MeToo, au-delà du hashtag - Lamy, Rose (Points Féministe, 2023)
En octobre 2017, #MeToo se propageait sur les réseaux sociaux, et le monde ne serait plus jamais comme avant. Si l’on sait que ce mouvement marquera l’histoire, on peine encore à en mesurer toutes les conséquences, tant il est en évolution permanente et ouvre des fronts de lutte multiples. Cinq ans plus tard, ce collectif dirigé par Rose Lamy réunit neuf femmes et autrices. Elles sont journalistes, militantes, musiciennes, étudiantes, philosophes, chercheuses ou essayistes, d’origine et d’âge différents, et portent un regard singulier sur cette révolution féministe. Le mouvement a-t-il réellement commencé en 2017 ? Y a-t-il eu une « vague » en France ? A-t-il profit à toutes les femmes ? Que veulent les victimes de violences sexistes ? Quelles forces s’organisent contre #MeToo ? À l’heure où le conservatisme reprend ses droits partout dans le monde, menaçant des acquis qu’on ne pensait plus avoir à défendre comme l’avortement, où le soupçon de mensonge ne cesse de peser sur les victimes, elles livrent chacune un point de vue documenté, urgent et passionné, au-delà du hashtag.
Keywords: #metoo; #moiaussi; 2000 à aujourd'hui; 2010-2019; 2020-2029; anthologie; approches et analyses; arts; communication; cours; discipline; droits des femmes*; essais; europe; france; histoire et politique; journalisme; justice sociale; patriarcat; point de vue situé; pol4212; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences; violences sexistes et sexuelles; études littéraires

Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

Dénoncer les féminicides des femmes autochtones aux États-Unis et au Canada La bande dessinée Deer Woman d’Elizabeth LaPensée, une super-héroïne autochtone éco-féministe ? - Bonadè, Sophie; Hamus-Vallée, Réjane; Journée-Duez, Aurélie (Genre en séries, 2019)
À travers l’analyse de la bande dessinée Deer Woman créée en 2015 par Elizabeth LaPensée (Anishinaabe, Canada), notre article a pour objectif principal d’interroger la notion de « super-héroïne » à l’aune de représentations autochtones engagées. Il s’agit de voir en quoi cette revitalisation du mythe traditionnel de la Femme Cerf (Deer Woman) interroge l’identité en termes de sexe et de genre, la culture et la place des femmes autochtones, en prenant une position radicale face au problème sociétal des féminicides en Amérique du Nord. Nous postulons que la figure de Deer Woman peut aussi être vue aujourd’hui comme une allégorie mettant en garde contre la domination masculine sur les femmes et sur toutes autres formes de vie. Tout d’abord, nous étudierons les caractéristiques formelles de Deer Woman et les mythes fondateurs autochtones qui en sont à l’origine. Nous montrerons ensuite en quoi cette super-héroïne dont les pouvoirs apparaissent après qu’elle a été sexuellement agressée, tend à dénoncer et lutter contre les féminicides touchant les femmes autochtones. Enfin, nous nous demanderons comment cette bande dessinée pourrait laisser entrevoir l’émergence d’une super-héroïne autochtone éco-féministe.
Keywords: amérique du nord; amériques; approches et analyses; arts; bande-dessinée; cours; discipline; environnement; féminicide; féminisme autochtone; féminisme pop; histoire et politique; justice sociale; militance; pol4105; premier cycle; racisme; régions géographiques; sexisme; super-héroïnes; système colonial; systèmes d'oppressions; thématiques; violences; écoféminisme; études littéraires

The winter we danced: voices from the past, the future, and the Idle No More movement - Kino-nda-niimi Collective (ARP Books, 2014)
"The Winter We Danced is a vivid collection of writing, poetry, lyrics, art and images from the many diverse voices that make up the past, present, and future of the Idle No More movement. Calling for pathways into healthy, just, equitable and sustainable communities while drawing on a wide-ranging body of narratives, journalism, editorials and creative pieces, this collection consolidates some of the most powerful, creative and insightful moments from the winter we danced and gestures towards next steps in an on-going movement for justice and Indigenous self-determination"
Keywords: 2000 à aujourd'hui; 2010-2019; DIG; amériques; approches et analyses; arts; canada; care; cours; créativité; discipline; féminisme autochtone; images; justice sociale; militance; musique; pol4105; poésie; premier cycle; périodes historiques; régions géographiques; santé; thématiques; études littéraires

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

The Native and the Refugee - Peterson, Matt; Rasamny, Malek (The Native and the Refugee)
A multi-media project profiling the spaces of the Indian reservation and Palestinian refugee camp: spaces of exception whose position in the struggle for native and Palestinian autonomy are essential. The Native and the Refugee will culminate in a feature-length documentary film.
Keywords: afrique; amérique du nord; amériques; approches et analyses; arts; arts visuels et médiatiques; camps de réfugiés; cours; discipline; documentaire; gaza; justice sociale; militance; palestine; pol5480; premier cycle; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; violences

Marguerite : la traversée | Épisode 2 - Transistor média
Émilie Monnet trace des parallèles entre la vie de Marguerite Duplessis et la cause des femmes, et plus particulièrement des femmes autochtones. Accompagnée de ses invité·e·s, Émilie parle de la tragédie des femmes disparues et de l’objectification dont elles sont encore victimes aujourd’hui,...
Keywords: 1700-1799; 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; arts; arts visuels et médiatiques; canada; cours; discipline; esclavage; féminisme autochtone; histoire et politique; justice sociale; martinique; performance; premier cycle; périodes historiques; québec; racisme; régions géographiques; sex2283; sexisme; système colonial; systèmes d'oppressions; thématiques; trafic sexuel; traite des femmes; violences; études littéraires